THE CONCEPT OF «NATIONAL SECURITY» WITHIN THE CATEGORICAL FRAMEWORK OF PUBLIC ADMINISTRATION - Liliia Muntian (Публічне управління та регіональний розвиток)
The article examines the concept of «national security» within the categorical framework of public administration, highlighting the absence of a universally accepted definition of «national security» and its role in public administration.